A methodological approach to utilize Egyptian colloquial Arabic as a source for ancient Egyptian linguistic analysis - Osman, Ahmed (AUC Knowledge Fountain, 2021)
Traces of the ancient Egyptian language can still be observed in modern Egyptian colloquial Arabic, which is the form of Arabic adopted by Egyptians as their native spoken language. This thesis aims to better understand the ancient Egyptian language through the analysis of its lexical survivals. It presents a new methodological approach to utilize ancient Egyptian lexical survivals as a source to study the ancient Egyptian language. A selected set of fifty-five ancient Egyptian lexical survivals was computed by matching ancient Egyptian and documented Egyptian colloquial Arabic words having the same semantic fields. While it was generally assumed that the only purpose of the ancient Egyptian lexical survivals into Egyptian colloquial Arabic was to describe items not available in the Classical Arabic lexicon (such as food items and agricultural tools specific to Egypt), analysis of the semantic fields of the computed ancient Egyptian lexical survivals rejects such an assumption. The thesis discusses other reasons for the lexical survival suggested by the language contact theory, including the native speakers’ desire to mark a separate identity. Qualitative analysis of the selected set of ancient Egyptian lexical survivals demonstrates the utilization of the modern usage of ancient Egyptian words to fine-tune our knowledge of ancient Egyptian lexical semantics. More precise meanings were suggested for the ancient Egyptian words šnꜤ, štm, mꜢꜢ, šd, dbdb, and imn. The thesis also employs contemporary Egyptian colloquial Arabic's orality to test several phonological assumptions of ancient Egyptian language and its diachronic evolution.